2017
DOI: 10.1111/zph.12381
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial resistance among Escherichia coli and Salmonella in Ontario smallholder chicken flocks

Abstract: SummarySurveillance is an important component of an overall strategy to address antimicrobial resistant bacteria in food animals and the food chain. The poultry market has many points of entry into the Canadian food chain, and some production practices are un- (1,022/1,025), and 47% (483/1,022) of positive E. coli isolates were resistant to one or more of the 14 antimicrobials. Furthermore, as compared to results reported for the CIPARS commercial flocks, E. coli isolates from smallholder flocks had significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
2
12
1
Order By: Relevance
“…in chicken meat and/or in any poultry products is relatively low compared to that of E. coli. [11,13,15] In this study, 18% (9 of 50 samples) prevalence of Salmonella spp. in chicken meat was recorded.…”
Section: Resultsmentioning
confidence: 49%
See 4 more Smart Citations
“…in chicken meat and/or in any poultry products is relatively low compared to that of E. coli. [11,13,15] In this study, 18% (9 of 50 samples) prevalence of Salmonella spp. in chicken meat was recorded.…”
Section: Resultsmentioning
confidence: 49%
“…in chicken meat was recorded. The study of Lebert et al [15] recorded 0.3% Salmonella prevalence at the bird level in smallholder flocks. Moawad et al [11] also reported 8.3% prevalence of Salmonella spp.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations